EFFORTS TO INCREASE STUDENT LEARNING INTEREST BY USING COOPERATIVE LEARNING MODEL BAMBOO DANCE TYPE ON BASIC COMPETENCIES OF PANCASILA AS THE BASIS OF PKN SUBJECTS IN GRADE VII SMP NEGERI 1 SIMANGUMBAN T.A 2017/2018 - Morris Gultom (Universitas Dharmawangsa, 2020)
The problem faced by the teacher was the problem of the low interest in student learning in Civics subjects in Class VIII of SMP Negeri 1 Simangumban. This study aims to determine whether using the cooperative learning model of the bamboo dance type can improve student learning interest in Civics in Class VIII of SMP Negeri 1 Simangumban in the 2017/2018 academic year. This type of research is